2022
DOI: 10.1007/s40119-022-00281-7
|View full text |Cite
|
Sign up to set email alerts
|

The Barriers to Rapid Reperfusion in Acute ST-Elevation Myocardial Infarction

Abstract: Introduction This study aimed to quantify the contribution of various obstacles to timely reperfusion therapy in acute ST-elevation myocardial infarction (STEMI) and to improve performance in a mixed remote rural/urban region. Methods From November 1, 2020 to April 23, 2021, patients with acute STEMI were prospectively monitored with the critical time intervals, treatment modalities, and outcomes registered. Selected clinical decision-makers in 11 hospitals were appoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In the most rural northern parts of Norway, fixed-wing air ambulance flight time to the nearest PCI centre varies from 20 to 75 min. 15 However, the speed of air travel may cause time optimism regarding the use of pPCI as the preferred strategy. An overly optimistic assumption that in-hospital fibrinolysis or pPCI could be administered in a timely manner was frequently a cause of delays in Northern Norway in 2020–2021.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the most rural northern parts of Norway, fixed-wing air ambulance flight time to the nearest PCI centre varies from 20 to 75 min. 15 However, the speed of air travel may cause time optimism regarding the use of pPCI as the preferred strategy. An overly optimistic assumption that in-hospital fibrinolysis or pPCI could be administered in a timely manner was frequently a cause of delays in Northern Norway in 2020–2021.…”
Section: Discussionmentioning
confidence: 99%
“…The explanations for this may be found at the system level. Bartnes et al 15 found that delayed establishment of a correct ECG diagnosis was the dominant cause of delayed fibrinolytic treatment. As in our study, they also found that a long time interval from symptom onset to FMC was an important obstacle, leaving some patients out of the 3-hour window where fibrinolysis has its best effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations